Influence of the Isothermal Transformation Temperature on the Structure and Properties of Low-Carbon Steel - Vakulenko, I. A.; Plitchenko, S. O.; Asgarov, K.; Lytvynov, B. V.; Orak, A.; Umur, H. (Science and Transport Progress, 2024)
Purpose. The study is aimed at evaluating the effect of the isothermal transformation temperature on the structure and properties of low-carbon steel. Methodology. The material for the study was a 3 mm diameter wire made of mild steel with the following chemical composition: 0.21% C, 0.47% Mn, 1.2% Si, 0.1% Cr, 0.03% S, 0.012% P. The 0.3 m long wire samples were subjected to austenitizing at 920 °C for 8...9 min, after which they were held isothermally for 11 min at temperatures of 650...200 °C, followed by cooling in air. The strength, plastic properties, and strain hardening coefficient were determined from the analysis of tensile curves. Findings. It was found that a decrease in the temperature of isothermal transformation, starting from 450...400 °C, increases the amount of Widmannstätten ferrite due to the disappearance of polyhedral ferrite grains. At the same time, the number of areas with locally located dispersed cementite particles similar to pearlite colonies increases, and bainite crystals appear. Against the background of a sharp decrease in the strain hardening coefficient in the range of 450...400 °C, the ability of the bainite phase to undergo plastic deformation should be considered one of the reasons for the delay in density reduction. Originality. The effect of steel hardening with a decrease in the pearlite transformation temperature is based on the grinding of ferrite grains, an increase in the amount of Widmannstätten ferrite, and the dispersion of pearlite colonies. The strengthening effect of steel with a bainite structure is based on an increase in the degree of supersaturation of the solid solution with carbon atoms and dispersion hardening by particles of the carbide phase. Practical value. The optimal structural state of steel intended for the manufacture of such critical elements as a support beam, railroad car bogie, etc. is a mixture of phase components with different dispersion and morphology, and their quantitative ratio is determined by the operating conditions of a particular product.